Hubungan Antara Kolaborasi Antar Siswa Dengan Hasil Belajar Fisika Pada Materi Gerak Di Kelas Viii Smp Negeri 4 Padangsidimpuan - Abdul Hadi; Eni Sumanti Nasution; Sri Utami Kholilla Mora Siregar (Universitas Gara Nusantara Padangsidimpuan, 2025)
This study aims to determine the relationship between student collaboration and physics learning outcomes on the topic of motion among eighth-grade students at SMP Negeri 4 Padangsidimpuan. A quantitative correlational method was applied with a sample of 30 students selected through purposive sampling. Collaboration data were collected using a validated 25-item questionnaire, while learning outcomes were obtained from report scores related to motion concepts. Data analysis included descriptive statistics, normality testing, linearity testing, and Pearson Product Moment correlation. The results show that student collaboration is categorized as high, with an average score of 95.47. Physics learning outcomes also fall into the high category, with an average score of 78.83. The correlation analysis revealed a strong and significant positive relationship between student collaboration and learning outcomes (r = 0.718; p < 0.01). The coefficient of determination indicates that collaboration contributes 51.6% to learning outcomes. This study highlights the essential role of collaborative learning in improving physics achievement in junior high schools.